PENGARUH PENERAPAN E-FILING, E-BILLING DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Hasan, Julian Muhammad; Septiningrum, Liana Dwi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to analyze the effect of implementing e-filing, e-billing and tax sanctions systems on taxpayer compliance at KPP Pratama Serpong using a quantitative approach. The research population is registered taxpayers at KPP Pratama Serpong. Primary data was obtained through questionnaires to respondents. Samples were taken using the convenience sampling method using the Slovin formula, resulting in 110 samples. Data analysis used multiple linear regression with SPSS version 20. The results showed that the implementation of the e-filing system had a positive effect on taxpayer compliance, while the implementation of the e-billing system had no effect, and the application of tax sanctions had an effect on taxpayer compliance.